Quasioptical Resonant System for Semiconductor Oscillators - Arkhipov, A. V.; Belous, O. I.; Kuzmichev, I. K.; Tischenko, A. S. (Видавничий дім «Академперіодика», 2013)
An open resonator loaded with the section of the oversize coaxial waveguide is described and analyzed. The resonator can be used as an oscillating system for solid-state millimeter wave generators.